THE INFLUENCE OF FINANCIAL INCLUSION, INNOVATION, FINTECH, PERCEIVED BENEFIT, AND PERCEIVED RISK ON THE FINANCIAL PERFORMANCE OF MSMEs IN MEDAN CITY - Tanady, Alvin; Ariesa, Yeni; Rischa, Rischa; Wati, Fenny; Fong, Fandi; Sahbana, Agung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to examine the impact of Financial Inclusion, Innovation, Fintech, Perceived Benefit, and Perceived Risk on the Financial Performance of UMKM in Medan City. The research method used is associative research (relationship analysis). The population in this study consists of UMKM owners in Medan City. The sampling technique applied is Accidental Sampling, with a total of 100 respondents, excluding 30 respondents used for validity testing. The data analysis method employed is multiple linear regression.The results of the F-test show that the F-calculated value (18.617) is greater than the F-table value (2.31) with a significance level of < 0.05, indicating that Financial Inclusion, Innovation, Fintech, Perceived Benefit, and Perceived Risk simultaneously have a significant influence on the Financial Performance of UMKM in Medan City. The t-test results reveal that Financial Inclusion has a positive and significant effect, Innovation has a negative and significant effect, Fintech has a positive and significant effect, Perceived Benefit has a positive and significant effect, and Perceived Risk has no effect on the Financial Performance of UMKM in Medan City. The coefficient of determination analysis shows an Adjusted R² value of 0.471, indicating that 47.1% of the variation in Financial Performance is explained by Financial Inclusion, Innovation, Fintech, Perceived Benefit, and Perceived Risk variables, while the remaining 52.9% is explained by other variables.